Quinazoline-sulfonamides as potential antitumor agents: synthesis and biological testing. (April 2013) - Alafeefy, Ahmed M.; Alqasoumi, Saleh I.; Ashour, Abdelkader E.; Alshebly, Mashael M.
Abstract New series of quinazoline containing sulfonamide derivatives were prepared and screened for their antitumor activity. Four human cancer cell lines, namely, hepatoma cancer cell line (HepG2), breast cancer cell line (MCF-7), cervix cancer cell line (HeLa) and colon cancer cell line (HCT-8), were used to measure the cytotoxic activity. Compounds 8 and 21 exhibited remarkable antitumor activity almost similar to that of the standard drug (doxorubicin). Six compounds 16, 22, 23, 29, 30 and 33, showed considerable activity and few compounds were totally inactive.